The Role of Human Capital in Education, Environment, and Economic - Sri Harnani; Diah Rusminingsih; Lina Damayanti (Asia Pacific Journal of Management and Education (APJME), 2022)
Our objective was to validate a prior study's hypothesis about the link between human capital and various factors. We gather scientific papers from natural science, emerald, and google researchers, as well as books published by specialists in the disciplines of human capital, economics, and the environment, via a systematic examination of the literature. We do research beginning with a conceptualization of human capital and education. Following that, we investigate the relationship between the research system on education, economy, and the environment and the notion of human capital. We found that learning new things, acquiring experience, and using cutting-edge technology are all ways to boost human capital. Human capital is essential to economic growth in developing nations. It is detrimental to the economic growth of developing countries to improve their institutions and people. Pollution and the health consequences on children may alter the dynamics of family inequality. Assuming parental health care spending is ineffective, we propose an alternative policy mix that pays for additional medical expenses.